Automation of building a cartogram for ecological and economic feasibility of the lands with the agricultural determination - Shulgan, Roman; Yanchuk, Oleksandr; Kibukevich, Olena (Geodesy and Cartography, 2020)
The conceptual model of automated building of the cartogram of ecological and economic lands feasibility with the agricultural determination has been developed. The coding system for attributive characteristics of agroproductive groups of soils and reliefs has been proposed. The represented concept has been realized in the ModelBuilder module of the software product called ArcGIS with the help of creating an instrument to build the cartogram for the ecological and economic feasibility of lands in an automatic mode. As a result, the instrument, which allows the execution dividing the territory into the feasibility groups of lands, has been received basing on the input raster or vector values.